2(-2)-3+5y+6=8y-4(-2)+24

Simple and best practice solution for 2(-2)-3+5y+6=8y-4(-2)+24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-2)-3+5y+6=8y-4(-2)+24 equation:


Simplifying
2(-2) + -3 + 5y + 6 = 8y + -4(-2) + 24

Multiply 2 * -2
-4 + -3 + 5y + 6 = 8y + -4(-2) + 24

Reorder the terms:
-4 + -3 + 6 + 5y = 8y + -4(-2) + 24

Combine like terms: -4 + -3 = -7
-7 + 6 + 5y = 8y + -4(-2) + 24

Combine like terms: -7 + 6 = -1
-1 + 5y = 8y + -4(-2) + 24

Multiply -4 * -2
-1 + 5y = 8y + 8 + 24

Reorder the terms:
-1 + 5y = 8 + 24 + 8y

Combine like terms: 8 + 24 = 32
-1 + 5y = 32 + 8y

Solving
-1 + 5y = 32 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
-1 + 5y + -8y = 32 + 8y + -8y

Combine like terms: 5y + -8y = -3y
-1 + -3y = 32 + 8y + -8y

Combine like terms: 8y + -8y = 0
-1 + -3y = 32 + 0
-1 + -3y = 32

Add '1' to each side of the equation.
-1 + 1 + -3y = 32 + 1

Combine like terms: -1 + 1 = 0
0 + -3y = 32 + 1
-3y = 32 + 1

Combine like terms: 32 + 1 = 33
-3y = 33

Divide each side by '-3'.
y = -11

Simplifying
y = -11

See similar equations:

| 3x+7y=6 | | 9(x-2)-4=14 | | -9x+3+5x=2x-3x+3+7-2 | | -x-2y+z=-6 | | 3x/7-5=4 | | 9(x-1)+3x=-9x+5 | | 2x+4y-2z=6 | | 0.42x-5=4 | | x+3y-z=12 | | 5x-y+5z=30 | | 5x-2x+6-4+14=5x-3x+8 | | 3(g-7)-2=4 | | 16=-4-4x | | -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 | | 72+36=0 | | 5x-2+8=7x-4 | | 21=8x-75 | | 6a+5x=36 | | (4s+4)(4s-4)=0 | | 3x+y+z=14 | | (3r-1)(4r-3)=0 | | 15-8m=73 | | -8x+6x-7x=3x(4-3)-5x-15 | | 98p=197 | | 5/3= | | 170-2x=25x+20 | | -5=15+4x |

Equations solver categories